2011
DOI: 10.1093/pasj/63.3.527
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectrum of a Peculiar Supernova Remnant, G 359.1-0.5

Abstract: We present the Suzaku results of a supernova remnant (SNR), G 359.1−0.5 in the direction of the Galactic center region. From the SNR, we find prominent K-shell lines of highly ionized Si and S ions, together with unusual structures at 2.5-3.0 and 3.1-3.6 keV. No canonical SNR plasma model, in either ionization equilibrium or under-ionization, can explain the structures. The energies and shapes of the structures are similar to those of the radiative transitions of free electrons to the K-shell of He-like Si and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…Since the Fe abundance estimated by only Fe-L lines has a large uncertainty due to their incompleteness, we cannot conclude why the abundance of Fe is lower than expected. The recombination parameter (n e t ∼ 1.4 × 10 12 cm −3 s) is the largest among any RP discovered so far in MMSNRs (Yamaguchi et al 2009b(Yamaguchi et al , 2012Ozawa et al 2009;Ohnishi et al 2011;Sawada & Koyama 2012;Uchida et al 2012;Yamauchi et al 2013).The spectra of the SE and NW regions also show the RP. Since the extended OH emission reported in the NW region suggests the interaction with molecular clouds, slightly higher N H than SE would be reasonable.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since the Fe abundance estimated by only Fe-L lines has a large uncertainty due to their incompleteness, we cannot conclude why the abundance of Fe is lower than expected. The recombination parameter (n e t ∼ 1.4 × 10 12 cm −3 s) is the largest among any RP discovered so far in MMSNRs (Yamaguchi et al 2009b(Yamaguchi et al , 2012Ozawa et al 2009;Ohnishi et al 2011;Sawada & Koyama 2012;Uchida et al 2012;Yamauchi et al 2013).The spectra of the SE and NW regions also show the RP. Since the extended OH emission reported in the NW region suggests the interaction with molecular clouds, slightly higher N H than SE would be reasonable.…”
Section: Discussionmentioning
confidence: 83%
“…However, recent X-ray observations have revealed several SNRs that are in the recombination-dominated phase (IC 443, Yamaguchi et al 2009b;W 49 B, Ozawa et al 2009; G359.1−0.5, Ohnishi et al 2011;W 28, Sawada & Koyama 2012;W 44, Uchida et al 2012;G346.6−0.2, Yamauchi et al 2013). These recombining plasmas (RPs)…”
Section: Introductionmentioning
confidence: 99%
“…Through the interactions between the shock from the SNR and the molecular cloud, the γ−ray can be produced. By modeling the X-ray emission from G359.1-0.5, Ohnishi et al (2011) found that the plasma of this mixed-morphology (MM) SNR is over-ionized. This property has also been observed in other γ−ray emitting MM SNRs such as IC 443 (Yamaguchi et al 2009) and W49B (Miceli et al 2010).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Following these discoveries, many authors have reported the detection of similar recombining plasmas in other SNRs. To date, more than a dozen such SNRs have been identified (G359.1–0.5: Ohnishi et al ; W28: Sawada & Koyama ; W44: Uchida et al ; G346.6–0.1: Yamauchi et al ; CTB 37A: Yamauchi et al ; 3C 391: Ergin et al ; G290.1–0.8: Kamitsukasa et al ; N49: Uchida et al ; Kes 17: Washino et al ; G166.0+4.3: Matsumura et al ; 3C 400.2: Ergin et al ; N132D: Bamba et al ; HB21: Suzuki et al ; CTB 1: Katsuragawa et al ; HB9: Sezer et al ). It is notable that virtually all of these SNRs are associated with the so‐called mixed‐morphology (MM) class, characterized by a centrally peaked X‐ray profile and rim‐brightened radio emission (Rho & Petre ).…”
Section: Observational Progressmentioning
confidence: 99%